Challenges in early stage communication for startups: Two case studies - Andrea Rumler; Leo Schmidt; Alexander Zumdieck (PraxisWISSEN Marketing, 2019)
Start-ups are regularly facing special challenges when developing their communication policy. Very often, neither the founders nor the company name or the products are well-known. This is especially true in the earliest phase of start-ups which is being analyzed in this article. It is especially important to know your communicative target groups and to adapt the communicative measures accordingly. After an analysis of phases in founding start-ups as well as important target groups of communicative measures for start-ups, two practical examples are being introduced. In conclusion, recommendations for the communication policy of start-ups are derived. – – Startups sehen sich besonderen Herausforderungen bei der Ausgestaltung ihrer Kommunikation gegenüber. Oft sind weder die Gründer, noch der Unternehmensname und das Produkt bzw. die Produkte bekannt. Dies gilt insbesondere in der Frühphase der Unternehmensgründung, die in diesem Artikel beleuchtet wird. Es ist deshalb besonders wichtig, die kommunikativen Zielgruppen zu kennen und die kommunikativen Maßnahmen entsprechend anzupassen. Nach einer Analyse der Phasen der Unternehmensgründung sowie der wichtigsten Zielgruppen kommunikativer Maßnahmen von Startups werden zwei Fallbeispiele vorgestellt. Schließlich werden Empfehlungen zur Kommunikationspolitik von Startups abgeleitet.
Keywords: 650; Communication challenges; failure of startups; life-cycle of startups; startup; stakeholder